The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4999/uhod.1111
|View full text |Cite
|
Sign up to set email alerts
|

Generic Imatinib Mesylate is as Effective as Original Glivec in the Clinical Management of CML.

Abstract: Unsustainable drug prices in chronic myeloid leukemia (CML) and cancer may be causing harm to patients. The aim of this multicenter study is to assess the efficacy of generic imatinib mesylate (IM) over Glivec in terms of hematological, cytogenetic, and molecular responses in CML. The data of 120 CML patients, who were treated with generic or original form of IM, were obtained from six different hematology clinics in Turkey between the years of 2009-2014 and analyzed retrospectively. Initial evaluation reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Generic imatinib [61][62][63] is now available worldwide and generic dasatinib is soon to be released. Quality generics have advantages in that the cost of therapy is often significantly reduced, making the drugs more affordable and hence more available to patients with limited resources.…”
Section: Genericsmentioning
confidence: 99%
“…Generic imatinib [61][62][63] is now available worldwide and generic dasatinib is soon to be released. Quality generics have advantages in that the cost of therapy is often significantly reduced, making the drugs more affordable and hence more available to patients with limited resources.…”
Section: Genericsmentioning
confidence: 99%
“…Anecdotal experiences from case reports in adults receiving GI approved outside Canada and the European Union (EU) have described reduced efficacy and safety compared to BI, while two small case series reported equal efficacy of GI and BI (for more details see ). Studies from Canada, India, Iran, and Turkey have demonstrated GI therapy to be well tolerated in patients with CML . Supporting these findings, a single‐center Croatian study showed that equivalent doses of GI and BI result in comparable plasma concentrations and comparable clinical efficacy .…”
Section: Introductionmentioning
confidence: 85%
“…Studies from Canada, India, Iran, and Turkey have demonstrated GI therapy to be well tolerated in patients with CML. [16][17][18] Supporting these findings, a single-center Croatian study showed that equivalent doses of GI and BI result in comparable plasma concentrations and comparable clinical efficacy. 19 A recently published multicenter retrospective cohort study evaluated efficacy outcomes in 41 adult patients with CML.…”
Section: Studies Comparing Branded and Generic Imatinibmentioning
confidence: 90%
“…Their results showed that MMR rate at 36 months was 93.9% in patients treated with Glivec, compared to 86.5% in patients treated with front-line generic therapy. 13 The same study found that after 18 months, more patients on generic imatinib were switched to nilotinib, compared to patients on Glivec (5.9% vs. 1%, respectively). It is interesting to note that our study showed higher percentage of patients who switched to nilotinib in both studied groups (52% vs. 27%, respectively).…”
mentioning
confidence: 88%
“…[6][7][8][9][10] However, studies from Turkey, Canada, India, Bosnia and Herzegovina, and Iran showed that generic therapy is well tolerated in CML patients and that adverse effects are manageable with supportive care. [11][12][13][14][15] In this study, we compared clinical outcomes of patients who received first-line Glivec (Group 1) to patients who received first-line generic imatinib (Group 2) in Bosnia and Herzegovina after three years of therapy. Branded and generic imatinib was administered orally at dosage of 400 mg/day.…”
Section: Introductionmentioning
confidence: 99%